Thrombotic Thrombocytopenic Purpura: Treatment Options - Naylor, DO, Kathleen; Williams, DO, Tejumade; Witmer, DO, Larry (Osteopathic Family Physician, 2018)
Thrombotic Thrombocytopenic Purpura (TTP) is a rare blood disorder that results in tiny blood clots affecting small blood vessels. This leads to low levels of platelets (blood clotting cells) in the blood and numerous small red-purple skin discolorations. TTP can affect any organ system but typically affects the brain and the kidneys. While the cause of this condition is unclear, we do know that patients with this condition have low levels of certain chemicals in the blood that slow or stop clots from forming. When these low levels are present, multiple clots can form in the body. Patients with TTP may complain of fatigue, seizures, strokes, confusion, decreased urine output, and may have an enlarged spleen. After taking a history and doing a physical, your physician would confirm the diagnosis of TTP with blood work.